Fatwa DSN-MUI No. 04/DSN-MUI/IV/2000 tentang Murabahah: Refleksi Kritis terhadap Implementasi BSI Dimensi Ekonomi Islam - Arifin, Asriadi (Institut Agama Islam Negeri Parepare, 2023)
This research aims to examine the Implementation of DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 concerning Murabaha in terms of Islamic economic aspects. This type of research is descriptive qualitative to explain narratively the results of research that are more concrete and in-depth. The approach used is normative, namely studying the DSN MUI fatwa regarding murabahah contracts in mortgage products implemented by Bank BNI Syariah Parepare Branch, which today has transformed into Bank Syariah Indonesia. The research results were obtained by observing and using direct interviews with informants. The results of the study found that the housing implementation of Indonesian Islamic Bank (BSI) mortgage products was in line with the DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 concerning Murabaha which is based on the context of the customer's needs to realize falah welfare together based on the principles of Islamic economics.